Multiple Factors Associated With Child Abuse Perpetration: A Nationwide Population-Based Retrospective Study. Issue 11 (June 2021) - Chang, Cheng-Chen; Hsieh, Ming-Hong; Chiou, Jeng-Yuan; Huang, Hsiang-Hsiung; Ju, Po-Chung; Wang, Jong-Yi
Differences in child abuse perpetration between individuals with and without mental disorders remain obscure. This study compared the risk difference and further investigated the association between the category of mental disorders and child abuse perpetration. A total of 681, 970 adults from the 2002 to 2013 Taiwan National Health Insurance Research Database were analyzed, including 340, 985 patients with psychiatric disorders (International Classification of Diseases, Ninth Revision, Clinical Modification [ICD-9-CM] codes 290.x–319.x) and 340, 985 sex- and age-matched individuals without psychiatric disorders. Child abuse perpetration (ICD-9-CM N-codes 995.5x and E-code E967) was the outcome variable. Matched analyses indicated that the risk of child abuse among patients with psychiatric disorders (0.25%) was significantly higher than that among those without psychiatric disorders (0.16%; odds ratio [OR] = 1.464, p < .0001). Among the six categories of mental disorders, the prevalence rates of committing child abuse were significantly higher for personality disorders, substance use, and affective disorders (0.56%, 0.45%, and 0.40%, respectively; p < .0001). Compared with anxiety disorders, substance use disorders were significantly associated with higher odds of child abuse perpetration (OR = 2.032, p < .05), especially physical abuse (OR = 2.018, p < .0001). Psychiatric morbidity was associated with higher odds of child abuse, with substance use determined as the major risk category. Screening high-risk families by using the associated factors is crucial.